(untitled) - Bass, Len (Boston, 2003)
This book introduces the concepts and best practices of software architecture--how a software system is structured and how that system's elements are meant to interact.
Keywords: Software architecture,System design,Thiết kế hệ thống,Kiến trúc phần mềm